Potential health claims of durum and bread wheat flours as functional ingredients - Ciudad-Mulero, María (2020)
Wheat is an important cereal with a key role in human nutrition. In this study, dietary fiber (DF) and arabinoxylans of di erent durum (Triticum turgidum ssp. Durum L.) and bread (Triticum aestivum L.) wheat flours were analyzed in order to point out their potential nutritional and health claims allege according to the current European regulation (Regulation (EU) No 432/2012). Moreover, other bioactive compounds (phenolics and tocopherols) were quantified as a first approach to their phytochemical composition in the analyzed wheat varieties. DF was analyzed following AOAC enzymatic-gravimetric methods; arabinoxylans and total phenols were quantified by colorimetric methods; tocopherols were determined by HPLC; antioxidant activity was evaluated using three di erent in vitro assays. Insoluble DF was the prevailing fraction in all analyzed samples. Water extractable arabinoxylans were higher in durum wheat flours. Whole flours contained higher total phenolics compounds. Alpha-tocopherol was the major isoform. Whole flours showed higher antioxidant properties. According to the obtained results, it is possible to allege all approved health claims referred to wheat, since all analyzed samples, especially whole flour and bran fraction, showed potential health benefits, as functional ingredients or functional foods, related with their phytochemical composition.